Pierre Brunei, Don Quichotte et le roman malgré lui, Cervantes, Lesage, Sterne, Thomas Mann, Calvino, Paris, Klincksieck, 2006, σελ. 415. ISBN: 2-252-03561-7. - Ιωακειμίδου, Λητώ (Σύγκριση/Comparaison/Comparison, 2017)
Δε διατίθεται περίληψη.